Purification, crystallization and preliminary X-ray crystallographic analysis of the ATPase domain of human TAP in nucleotide-free and ADP-, vanadate- and azide-complexed forms - Meena, Sita R. (International Union of Crystallography, 2012)
The human transporter associated with antigen processing (TAP) protein belongs to the ATP-binding cassette (ABC) transporter superfamily and is formed by the heterodimerization of TAP1 and TAP2 subunits. TAP selectively pumps cytosolic peptides into the lumen of the endoplasmic reticulum in an ATP-dependent manner. The catalytic cycle of the ATPase domain of TAP is not understood at the molecular level. The structures of catalytic intermediates of the ATPase domain of TAP will contribute to the understanding of the chemical mechanism of ATP hydrolysis. In order to understand this mechanism, the ATPase domain of human TAP1 (NBD1) was expressed and purified, crystallized in nucleotide-free and transition-state complex forms and X-ray crystallographic studies were performed. The NBD1 protein was crystallized (i) in the nucleotide-free apo form; (ii) in complex with ADP–Mg(2+), mimicking the product-bound state; (iii) in complex with vanadate–ADP–Mg(2+), mimicking the ATP-bound state; and (iv) in complex with azide–ADP–Mg(2+), also mimicking the ATP-bound state. X-ray diffraction data sets were collected for apo and complexed NBD1 using an in-house X-ray diffraction facility at a wavelength of 1.5418 Å. The apo and complexed NBD1 crystals belonged to the primitive hexagonal space group P6(2), with one monomer in the asymmetric unit. Here, the crystallization, data collection and preliminary crystallographic analysis of apo and complexed NBD1 are reported.